Similarities and Differences in Alcohol Trajectories: Testing the Catch-Up Effect among Biracial Black Subgroups - Goings, Trenette Clark (Addict Behav, 2016)
Using National Longitudinal Study of Adolescent and Adult Health (Add Health) data, we examine the alcohol-use trajectories of monoracial Black youth and biracial Black-White, Black-Hispanic, and Black-American Indian youth to assess how their trajectories differ from the alcohol-use trajectories of White youth over time. The sample consists of 9,421 adolescents and young adults who self-identified as White, Black, Black-American Indian, Black-Hispanic, or Black-White. Study hypotheses are tested using latent growth curve modeling. Results indicate that a catch-up effect exists, but only for Black-American Indians whose alcohol-use rates approach the higher rates of Whites at age 29. Black-American Indians face particularly high risk of problematic drinking over the life course. Additional research is needed to understand causal factors of alcohol-use among biracial individuals particularly Black-American Indians who may be at higher risk for alcohol misuse.